Authenticity of Storial.co as Virtual Application in Creative Writing - Diah Anita Pusparini; Ana Ahsana El-Sulukiyyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2022)
Virtual applications in English Language Teaching are no longer a current issue to be applied in any class activities. Various types of applications are there and it needs the teachers’ hand to make use of them into proper way of teaching. Students are also at their wide chance to utilize technology independently as tools to study, especially language. Storial.co is one of the writing platforms which offer its users to read and write literature in the form of poem, short story, or even novel. Writing is considered a personal activity hence it needs time and space to gather the feelings and ideas into a composition. Through storial.co, students are able to write intensively at any place and time though some drawbacks may occur during the writing process. Using online questionnaire, a designated data related to the use of storial.co during the creative writing class is distributed to know whether students can utilize the platform at its most. As a final conclusion, significant implication is dedicated to the lecturer and students of creative writing to keep on using virtual application, especially writing platform to be able to sharpen the language use productively.